KONTUSIO LABIRIN PADA PASCA CEDERA KEPALA - Ari Astuti (Berkala Ilmiah Kedokteran Duta Wacana, 2019)
Background : Blunt head trauma without any temporal bone fracture or longitudinal temporal bone fracture, with an associated fracture of the labyrinth may cause labyrinthine injury with hearing loss and vertigo because of a concusive injury to the membranous labyrinth. Objective : To explain a case of labyrinthine concussion in patient with post traumatic brain injury experienced in Dr. Sardjito Hospital Yogyakarta. Case Description : A patient who treated in the hospital with spinning sensation after crush injury. She also had fracture of the left collum femur. Head CT scan and laboratory examination was initiated within normal limit. Patient then diagnosed with labyrinthine concussion and treated with symptomatic therapy and physiotherapy. Conclusion : Labyrinthine concussion can occur to the patient of blunt head trauma. Pharmacotherapy and physiotherapy should be initiated to reduce symptomps and uncomfortable sensation. Keywords : labyrinthine concussion, traumatic brain injury, mixed type vertigo